Intelligence science and big data engineering : 7th International Conference, IScIDE 2017, Dalian, China, September 22-23, 2017, Proceedings /: 7th International Conference, IScIDE 2017, Dalian, China, September 22-23, 2017, Proceedings. (2017) - Unknown
No abstract available